Possible links between Indonesian science teacher’s TPACK perception and demographic factors: Self-reported survey - Ibrohim, Ibrohim (Modestum LTD, 2022)
TPACK is a trending teacher expertise framework for teaching using digital technology. However, not many studies have revealed the relationship of the seven TPACK factors with demographic factors. This study aimed to determine the effect of gender, teaching experience, place of teaching, and level of education on the perception of TPACK for science teachers. A total of 1,357 high school science teachers were involved in this research. The survey data were analyzed using the Mann-Whitney U and Kruskal-Wallis tests. Overall results show that gender influences the perception of TPACK. On the teaching experience factor, teachers with less than five years of teaching experience have higher perceptions of TK, TPK, TCK, and TPACK. The teacher’s workplace significantly differs in perceptions of TK and TCK. Regarding education level, teachers with a master’s degree education have a higher and significantly higher TPACK perception than teachers with a bachelor’s degree.